The Influence of Service Quality and Brand Image on Repurchase Intention Mediated by Customer Satisfaction - Lestari, Putri Indah Dwi; Bertuah, Eka (Yayasan Gema Bina Nusantara, 2025)
The purpose of this study is to investigate the direct influence of service quality and brand image on customer satisfaction, to determine the direct influence of customer satisfaction, service quality and brand image, on repurchase intention. As well as the indirect influence of service quality and brand image on repurchase intention through customer satisfaction at Ayam Gepuk Pak Gembus (AGPG) outlets. Data collection was carried out using a questionnaire distributed online using Google Forms through social media such as Whatsapp and Instagram. The population in this study were all customers of AGPG outlets. The questionnaires collected were 190 respondents and the data were processed using the Smart PLS analysis tool. From the results of this study, it was found that service quality has a positive effect on customer satisfaction. Brand image has a positive effect on customer satisfaction. Customer satisfaction has a positive effect on repurchase intention. Service quality has no effect on repurchase intention. Brand image has a positive effect on repurchase intention. Service quality has an effect on repurchase intention through customer satisfaction. Finally, brand image has an effect on repurchase intention through customer satisfaction. Therefore, it is important for Ayam Gepuk Pak Gembus to improve the quality of service better with the aim of improving the brand image that has been formed at AGPG, so that customers will feel satisfied in visiting and purchasing at the outlet and have an interest in repurchasing products at the AGPG outlet.